Attitudes Towards Mathematics in Future Teachers: EAHM-U Scale Colombian Adaptation - Ávila-Toscano, José Hernando; Vargas-Delgado, Leonardo José; Alonso-Miranda, Marien Fernanda; De La Cruz-González, Jean Carlos (Revista Electrónica Educare, 2023)
Introduction. Positive and negative attitudes influence the teaching-learning processes of mathematics, so this study focused on analyzing the psychometric properties of the Attitudes Toward Mathematics Scale (EAHM-U) in Colombian university students to provide a context-adjusted and truly validated measurement tool. Method. An instrumental design was used with 446 undergraduate mathematics students to analyze the factor structure and internal consistency of the instrument scores. Results. a 13-item instrument with two dimensions called benefit from mathematics and difficulty in learning mathematics was obtained. Discussion. The modified scale presents adequate psychometric qualities, favorable levels of reliability in the scores, and indicators of replicability, suggesting that the items measure each dimension appropriately.